2020
DOI: 10.1093/aob/mcaa089
|View full text |Cite
|
Sign up to set email alerts
|

V-Mango: a functional–structural model of mango tree growth, development and fruit production

Abstract: Background and Aims Mango (Mangifera indica L.) is the fifth most widely produced fruit in the world. Its cultivation, mainly in tropical and sub-tropical regions, raises a number of issues such as the irregular fruit production across years, phenological asynchronisms that lead to long periods of pest and disease susceptibility, and the heterogeneity of fruit quality and maturity at harvest. To address these issues, we developed an integrative functional–structural plant model that synthesiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 65 publications
0
22
0
Order By: Relevance
“…These models typically predict fruit growth through the consideration of the tree as a set of subunits competing for resources such as light, photo-assimilates and water. The QualiTree model is probably the most advanced tree fruit mechanistic model, although attempts for other tree crops are advancing, e.g., for mango [6,7].…”
Section: Types Of Modelsmentioning
confidence: 99%
“…These models typically predict fruit growth through the consideration of the tree as a set of subunits competing for resources such as light, photo-assimilates and water. The QualiTree model is probably the most advanced tree fruit mechanistic model, although attempts for other tree crops are advancing, e.g., for mango [6,7].…”
Section: Types Of Modelsmentioning
confidence: 99%
“…Previous models evaluating the effect of stem diameter in current year branches revealed that they may predict leaf and branch conductivity (Normand and Lauri, 2012; Boudon et al ., 2020). However, this refers to the conductivity of the xylem, which constitutes most of the branch mass.…”
Section: Discussionmentioning
confidence: 99%
“…Previous models evaluating the effect of stem diameter in current year branches revealed that they may predict leaf and branch conductivity (Normand and Lauri, 2012;Boudon et al, 2020).…”
Section: Conductivity Of the Sieve Tubes In The Stems Of Mangomentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the knowledge of architecture and functioning of the fruit tree was developed with the aim of analyzing genetic diversity of tree shape and fruit production (Lauri and Laurens, 2005) and deciphering genetic mechanisms underlying architectural (Hollender and Dardick, 2015) and functional (e.g., hydraulics; Lauri et al, 2011) traits. These studies contributed to the development of functional structural plant models (FSPM) aimed at integrating relationships between plant architecture and physiological functions that ultimately underlie growth and development (Boudon et al, 2020). From an applied point of view, such studies are also at the origin of novel architectural‐based fruit‐tree management proposals in orchards (Lauri, 2019).…”
Section: Architecture and Functioning Of The Fruit Treementioning
confidence: 99%